Peace in emptiness - Yeo, Shi Qing (Nanyang Technological University, 2024)
From the late 1990s to early 2000s, scholars engaged in a wide-ranging discussion about Tang dynasty (tangchao 唐朝) poet, Wang Wei’s 王維 (701-761) poetry, and its relation to Buddhist thought, particularly his nature poems and their connection to Chan 禪 Buddhist doctrines. Methods and data used in debating the influence of Buddhism on Wang Wei’s poetry include examination of Wang Wei’s personal beliefs, family backgrounds, connections with monks, poems that contain several Chan Buddhist-related terms, the majority of which are not obviously related to Chan Buddhist doctrines. However, the recent development of digital humanities approaches offers quantitative approaches to this discussion, which I apply in this study. This paper identifies dominant scholarly positions on Wang Wei and his poetry in relation to Chan Buddhism of his time, and introduces a new methodological approach, Docusky, to conduct a quantitative analysis of the Chan Buddhist vocabulary in Wang Wei’s poems, which will contribute to the Wang Wei discussion. The findings from Docusky reveal a wide range of Chan Buddhist-related terms in Wang Wei’s poetry, which will be used to detail the intricacies of certain terms that most scholars associate with Chan Buddhism. While the discussion about whether Wang Wei truly intended Chan Buddhist significance in his poetry is intriguing, this paper believes that the focus should be on when, why and how Wang Wei’s gained his title as the Buddha of Poetry.